2018
DOI: 10.1186/s12957-018-1411-9
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic ureteroscopy before radical nephroureterectomy in upper urinary tract urothelial carcinoma is not associated with higher intravesical recurrence

Abstract: BackgroundTo clarify if diagnostic ureteroscopy (URS) before radical nephroureterectomy for patients with upper tract urothelial carcinoma (UTUC) will increase the risk of intravesical recurrence.MethodsFrom retrospective review of cohort at our institution, 502 patients with UTUC who underwent radical nephroureterectomy with bladder cuff excision were enrolled from 1990 to 2013. Cox proportional hazards model was used to analyze the overall survival (OS), disease-free survival (DFS), metastasis-free survival … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
54
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(56 citation statements)
references
References 30 publications
0
54
0
2
Order By: Relevance
“…In addition, after multivariate analysis with adjustment for confounding factors, prior history of bladder UC and concurrent bladder UC were independent risks for intravesical recurrence for all UTUC. A large cohort study focusing on the impact of diagnostic ureteroscopy after RNU also found that bladder UC was the main risk for intravesical recurrence but not diagnostic urteroscopy 23 . To date, the pathophysiology or mechanism of lower tract seeding of urothelial cancer still remains unclear and most of the published evidences that favored diagnostic ureteroscopy as a risk factor were biased due to not excluding cases with prior bladder UC 23 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, after multivariate analysis with adjustment for confounding factors, prior history of bladder UC and concurrent bladder UC were independent risks for intravesical recurrence for all UTUC. A large cohort study focusing on the impact of diagnostic ureteroscopy after RNU also found that bladder UC was the main risk for intravesical recurrence but not diagnostic urteroscopy 23 . To date, the pathophysiology or mechanism of lower tract seeding of urothelial cancer still remains unclear and most of the published evidences that favored diagnostic ureteroscopy as a risk factor were biased due to not excluding cases with prior bladder UC 23 .…”
Section: Discussionmentioning
confidence: 99%
“…A large cohort study focusing on the impact of diagnostic ureteroscopy after RNU also found that bladder UC was the main risk for intravesical recurrence but not diagnostic urteroscopy 23 . To date, the pathophysiology or mechanism of lower tract seeding of urothelial cancer still remains unclear and most of the published evidences that favored diagnostic ureteroscopy as a risk factor were biased due to not excluding cases with prior bladder UC 23 . In brief, it is still controversial as to whether diagnostic ureteroscopy is a major reason increasing the risk of intravesical recurrence, and a well designed randomized trial is mandatory to answer this unsolved issue.…”
Section: Discussionmentioning
confidence: 99%
“…They concluded that URS is not an independent risk factor for IVR. In another cohort study, the authors found that URS prior to RNU was not associated with a higher risk of IRFS even in patients without a history of bladder cancer [26]. Yoo et al [27] investigated whether biopsy during URS for UTUC before RNU affected IVR.…”
Section: Discussionmentioning
confidence: 99%
“…In one study of 502 patients, of whom 206 underwent preoperative URS (Pre-U) and 296 did not (Non-U), Pre-U did not increase the risk for IVR (HR, 1. 136; 95% confidence interval [CI], 1.00-1.30; p=0.059) [3]. Another meta-analysis showed that Pre-U before RNU did not negatively affect overall survival, recurrencefree survival, cancer-specific survival, or metastasis-specific survival [4].…”
Section: Impact Of Diagnostic Ureteroscopy Before Radical Nephrouretementioning
confidence: 99%